Recurrent gastric antral vascular ectasia: a single center experience - Cavallaro, Andrea; Zanghì, Antonio; Di Vita, Maria; Catania, Vito Emanuele; Longo, Giovanni; Lo Menzo, Emanuele; Granata, Roberta; Valenti, Maria Rosaria; Cappellani, Alessandro; Di Majo, Simone (Frontiers in Surgery, 2024)
Introduction Gastric antral vascular ectasia (GAVE) is a rare cause of chronic or acute gastrointestinal bleeding. This condition accounts for ∼4% of upper gastrointestinal bleeding cases. This disease is often associated with systemic diseases, such as liver cirrhosis, chronic kidney failure, autoimmune conditions, diabetes mellitus, hypothyroidism, and cardiovascular diseases. However, its etiopathogenesis remains controversial. Materials and method We retrospectively reviewed the cases of GAVE treated at our digestive surgery unit. A total of nine patients were identified with a male/female ratio of 1.25:1 and an average age of 75.51 years (SD ± 9.85). All patients underwent endoscopic argon plasma coagulation (APC) treatment. At the time of the review, data on eight patients were available after 36 months of follow-up. Results APC appears to be safe and effective for hemostasis of bleeding vascular ectasia. Only one (11.1%) patient required surgical intervention due to hemodynamic instability after multiple unsuccessful endoscopic treatments. No intraoperative and postoperative complication or bleeding relapse was experienced. Discussion Based on our findings, we concluded that endoscopic APC is technically simple, but requires multiple re-interventions due to the incidence of relapses. Furthermore, larger randomized studies should be conducted to assess the role of elective surgery as the first intervention in stable patients with severe pathology and the timing of surgery after failed endoscopic treatment.